Inoculum development for lipid and gamma linoenic asid production by Cunninghamella bainieri2A1) - Farhila Muhid,; Abdul Jalil Abdul Kader,; Wan Mohtar Wan Yusoff,; Othman Omar,; Aidil Abdul Hamid, (Universiti Kebangsaan Malaysia, 2012)
Inoculum for a local isolate of oleaginus fungi, Cunninghamella bainieri 2A1 was developed by establishing the inoculum types, age and size for growth, lipid and gamma linolenic acid (GLA) production. Cultivation was carried out in 500 mL shake flask containing 200 mL of nitrogen limiting medium at 30°C and 250 rpm agitation. Direct inoculation of spores into the production cultures gave higher productivity of lipid production 0.71 (g/L/day) than using 24 and 48 vegetative cells cultures which gave only 0.51 and 0.45 (g/L/day), respectively. Besides, production of GLA (5.3 × 10-2 g/g lipid less biomass) in the cultures which directly inoculated with spores (1 × 105 spores/mL) was 23% higher than those produced in the cultures started with vegetative cells. Spore concentration of 1 × 103 spores/mL produced pelletal growth in size of 1.04 mm which contain 40% (g/g biomass) lipid and 8.34 × 10-2 (g/g lipid less biomass).